Kaplun P.V., Gonchar V.A. Complex criterion of assessment of contact experience of structural elements with nitrogen coatings at termination. - Каплун, П.В.; Гончар, В.А. (Problems of Tribology, 2017)
The complex coefficient of estimation of quality of composition is offered it is "nitrided coverage-basis" taking into account the thickness of coverage, hardness of surface and basis,gradient of hardness of coverage and maximal remaining tensions in coverage on the criterion of her maximal pin endurance at the friction of woobling.Key words: coverage, coefficient, basis, quality, gradient.